The higher the household income, the lower the possibility of depression and anxiety disorder: evidence from a bidirectional Mendelian randomization study - Liu, Guangyan; Liu, Wenlin; Zheng, Xifeng; Li, Junyan (Frontiers in Psychiatry, 2023)
Objectives: Observational studies have demonstrated that household income is associated with morbidity of mental disorders. However, a causal relationship between the two factors remains unclear. Therefore, we investigated the causal relationship between household income status and genetic liability of mental disorders using a bidirectional Mendelian randomization (MR) study. Methods: This MR study included a large cohort of the European population from publicly available genome-wide association study datasets. A random-effects inverse-variance weighting model was used as the main standard, with MR-Egger regression, weighted median, and maximum likelihood estimations performed concurrently as supplements. Sensitivity analysis, consisting of heterogeneity and horizontal pleiotropy tests, was performed using Cochran’s Q test, MR-Egger intercept, and MR-PRESSO tests to ensure the reliability of the conclusions. Results: A higher household income tended to be associated with a lower risk of genetic liability for depression (odds ratio [OR]: 0.655, 95% confidence interval [CI]=0.522–0.822, P<0.001) and anxiety disorder (OR: 0.666, 95% CI=0.526–0.843, P<0.001). No associations were observed for schizophrenia (OR: 0.678, 95% CI=0.460–1.000, P=0.05), panic disorder (OR: 0.837, 95% CI=0.445–1.577, P=0.583), insomnia (OR: 1.051, 95% CI=0.556–1.986, P=0.877), obsessive-compulsive disorder (OR: 1.421, 95% CI=0.778–2.596, P=0.252), and bipolar disorder (OR: 1.126, 95% CI=0.757–1.677, P=0.556). A reverse MR study showed no reverse causal relationship between psychiatric disorders and household income. Sensitivity analysis verified the reliability of the results. Conclusions: Our results revealed that the population with a higher household income tended to have a minor risk of genetic liability in depression and anxiety disorders.